American Politics and Government - Beaubien, Anne K.; Michigan Univ., Ann Arbor. Univ. Libraries ([Washington : Clearinghouse, 1988)
This selective, annotated bibliography focusing on American politics and government has been compiled to aid graduate students in political science research. Emphasis has been placed on key indexes, bibliographies, and guides. (Author/MBR)
Microfiche.
Keywords: Annotated Bibliographies; Political Science; Reference Materials, Bibliographies